2001
DOI: 10.1093/geronb/56.6.s352
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptomatology in Middle-Aged and Older Married Couples: A Dyadic Analysis

Abstract: Results highlight the importance of dyadic data and multilevel models for understanding depressive symptomatology in married couples. The influence of race/ethnicity merits greater attention in future research. Differences in findings between HRS and AHEAD suggest life-course, cohort, or methodological influences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 75 publications
12
118
1
Order By: Relevance
“…Townsend et al also found out that being married is protective against the development of depressive symptoms. 23 Bulloch et al, Akhtar et al, Kessler et al also implicated that married persons will be able to cop up with emotional stressors than non-married couples. 19,24,25 Smoking and Alcoholism were the habitual factors studied in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Townsend et al also found out that being married is protective against the development of depressive symptoms. 23 Bulloch et al, Akhtar et al, Kessler et al also implicated that married persons will be able to cop up with emotional stressors than non-married couples. 19,24,25 Smoking and Alcoholism were the habitual factors studied in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, older couples share a long history of joint experiences typically originating from several decades of life [7,40] . Figure 1 illustrates past research which points to spousal similarities and interrelations in cognitive functioning [41][42][43] , well-being, and health [29,44,45] .…”
Section: Spousal Interrelations In Old Age: Findings From Three Domaimentioning
confidence: 99%
“…Consequently, a considerable body of research addresses emotional experiences in partnerships [for an overview, see 10 ]. Several large-scale studies point to spousal interrelations in well-being and depression in old age [45,[65][66][67][68] ( fig. 1 ).…”
Section: Spousal Interrelations In Well-beingmentioning
confidence: 99%
“…Researchers have found the well-being of one member of the care dyad to be significantly associated with the well-being of the other member (Bookwala & Schulz, 1996;Lyons, Zarit, Sayer, & Whitlatch, 2002;Townsend, Miller, & Guo, 2001). Recently, family care research has moved towards a greater emphasis on the interactive and dynamic processes of the care situation.…”
Section: Need For a Dyadic Contextmentioning
confidence: 99%